2015
DOI: 10.1021/acs.oprd.5b00150
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acids and Derivatives—Probing the Structure–Activity Relationships for Mutagenicity

Abstract: Despite a recent publication describing boronic acids as a "novel class of bacterial mutagen," process and analytical chemists may not be aware of the potential worker exposure hazards, or of the need to assess boron compounds as potential genotoxic impurities (GTIs) per ICH M7. This publication provides new Ames data for 44 commercially available boronic acids, boronic acid derivatives, and boron containing reagents. Trends in the Ames data are discussed from a structure-activity perspective. Common reagents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 56 publications
0
60
0
Order By: Relevance
“…However, much work remains to be done in this field. Some other results suggest that oxidation of boron compounds can generate organic radicals as a potential mechanism for mutagenicity (Hansen, 2015).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 99%
See 3 more Smart Citations
“…However, much work remains to be done in this field. Some other results suggest that oxidation of boron compounds can generate organic radicals as a potential mechanism for mutagenicity (Hansen, 2015).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 99%
“…Considering the doses employed, the results of several studies strongly suggest that these compounds do not produce toxic effects in humans (SorianoUrsúa, 2014a;Sanjoh, 2014;Fu, 2014). Moreover, it is known that they have a low mutagenic or cytotoxic effect (O'Donovan, 2011;Hansen, 2015;Pellizzaro, 2015;Scott, 2015). O'Donovan et al (2011) reported that a number of aryl boronic acids have low or null mutagenic effects.…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…4 These results are further strengthened by a recent study that discloses the mutagenicity associated with a large number of boronic acids, esters, MIDA boronates, potassium trifluoroborates, as well as their precursors bis(pinacolato)diboron and bis-boronic acid. 5 The newly-assessed genotoxicity of boron compounds naturally poses some serious limitations to their applications in medicinal and process chemistry, both in terms of worker exposure hazards and more stringent standards of purity to avoid the persistence of genotoxic impurities. It is foreseeable that these findings will stress the necessity of a paradigm shift and prompt the organic synthetic community to appreciate the advantages and potentials of other classes of donors in cross-coupling processes, including silicon.…”
Section: Introductionmentioning
confidence: 99%